Peningkatan Kemandirian Belajar Pendidikan Agama Katolik Dengan Model PBL Pada Materi Kemampuanku Dan Keterbatasanku Fase D - Sadawa, Irene Mariana; Lede, Yohanes Umbu (Varied Knowledge Journal, 2024)
This study aims to determine the improvement of PAK Learning Independence with PBL Model on the Material of My Ability and My Limitations Phase D Class VII. This study used a class action research method carried out in two cycles. Each cycle consists of four stages, namely planning, implementation, observation and reflection. The results of the research during the two cycles showed, in cycle 1 still did not achieve maximum results this was because students were still new to the PBL learning method with the achievement of 70% results. This situation is also likely to occur because the previous teacher in his teaching used the lecture method during the process of learning activities at school. However, a significant increase occurred in the second cycle of 85%. This shows that if the PBL learning method is applied well and consistently, it will improve student learning outcomes.